2002
DOI: 10.1039/b109953c
|View full text |Cite
|
Sign up to set email alerts
|

Glucose oxidase catalyses the reduction of O2 to H2O2 in the presence of irradiated TiO2 and isopropyl alcohol

Abstract: Catalytic amounts of glucose oxidase from Aspergillus niger (GO) are active in the reduction of O2 to H2O2 in the presence of irradiated suspensions of TiO2 and isopropyl alcohol as electron donor. An explanation of this behaviour is given on the basis of the ability of the enzyme to capture electrons from the photoexcited TiO2 instead of its natural substrate, glucose. This process has a marked positive effect on both the oxidation of isopropyl alcohol to acetone and the formation of radical intermediates, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…5C the results obtained with 2-propanol already published in Ref. [22]. We observe that in all cases the formation rate of the adducts between pbn and the alkoxy radicals increases significantly in the presence of GO, thus indicating that in any case the enzyme has a positive effect on the oxidation rate of the alcoholic substrate to the corresponding radical species.…”
Section: Alcohols Oxidationsupporting
confidence: 70%
See 4 more Smart Citations
“…5C the results obtained with 2-propanol already published in Ref. [22]. We observe that in all cases the formation rate of the adducts between pbn and the alkoxy radicals increases significantly in the presence of GO, thus indicating that in any case the enzyme has a positive effect on the oxidation rate of the alcoholic substrate to the corresponding radical species.…”
Section: Alcohols Oxidationsupporting
confidence: 70%
“…Therefore, we expected that the presence of the enzyme may also affect the photocatalytic properties of this semiconductor towards organic substrates that can be oxidized by these reactive intermediates. We have previously found that GO has a marked positive effect on the oxidation of 2-propanol [22]. Herein, this study is extended to other alcoholic substrates.…”
Section: Alcohols Oxidationmentioning
confidence: 91%
See 3 more Smart Citations